A camouflage conundrum: unexpected differences in winter coat color between sympatric species. Issue 3 (18th March 2019) - Davis, Brandon M.; Kumar, Alexander V.; Mills, L. Scott
Abstract: Across the globe, more than 21 species undergo seasonal changes in coloration, molting white in winter to become camouflaged against snow. Given the adaptive value of seasonal camouflage against local snow duration, one might predict that sympatric coat color changing species would have similar winter coat color. This hypothesis, however, contrasts with anecdotal evidence and modeling results that predict sympatric winter white and winter brown species in some areas with transient snow cover. In one such area, West Virginia, we document coat color phenology between three sympatric species: snowshoe hares ( Lepus americanus ), long‐tailed weasels ( Mustela frenata ), and least weasels ( Mustela nivalis ). Using a combination of field methods, we document and quantify each species' winter coat color, illustrating an interspecific polymorphic response in winter coloration among sympatric winter white snowshoe hares and winter brown weasels. We then hypothesize what forces drive the interspecific differences between snowshoe hare and weasel winter coloration, highlighting areas of focus for future seasonal coat color research.